Applying the expert-novice paradigm in tennis coaching: improving coaches' knowledge, diagnostic skills and understanding of the tennis serve technique - Fetisova, Y. (Victoria University, 2021)
Tennis coaches` technical knowledge plays a critical part in performance analysis as it impacts their recommendations to athletes. To date, the research on tennis coaches` knowledge is limited, and no previous studies have attempted to examine expert tennis coaches` knowledge and diagnostic ability of the tennis serve technique. This research aimed to examine the knowledge and diagnostic ability of expert and novice tennis coaches, and to identify the key distinguishing characteristics between expert and novice tennis coaches. As a result, the key distinguishing characteristics between expert and novice tennis coaches were identified, and there was a recognised need to develop an online training course to improve coaches` knowledge and understanding of the tennis serve technique. An online coach education course was then developed, and the effectiveness of the course was evaluated. This thesis comprised three studies employing a mixed-methods design. Data was collected and analysed by using both qualitative and quantitative methods to gain a deeper understanding of novice and expert tennis coaches` knowledge, diagnostic skills and learning. The main data collection methods were in-depth interview and an online questionnaire that was constructed specifically for this investigation. Pre- and post-intervention design was used to investigate the efficacy of a training intervention on coaches` knowledge and their diagnostic ability of the tennis serve technique. A video-based test was developed to measure the effectiveness of the online course. As a result of the first two studies, models representing declarative and practical knowledge of expert and novice tennis coaches were developed. The key distinguishing characteristics between novice and expert coaches were that experts displayed a superior understating of the functionality of the tennis serve technique and an advanced diagnostic ability. Expert coaches were able to see the tennis serve as "a whole" in comparison with novices who focused more on separate technical elements. It was suggested that novice coaches need to develop the knowledge of tennis serve from two perspectives: technical and functional. The findings of this thesis extend our current understanding of tennis coaches` knowledge and diagnostic skills. The development and evaluation of an online training course provides a unique contribution to coach education in order to understand the cause-and-effect relationships between technical elements withing the flat serve should allow tennis coaches to prescribe more effective training interventions. By knowing how one element may affect another, coaches will be able to identify and rectify technical issues by addressing the cause of the problem instead of focusing on many separate elements. The design of this program can also be used with other technical elements in tennis and can be applied to other sports to improve coaches` knowledge and diagnostic ability of sport technique.